2019
DOI: 10.1002/gepi.22209
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of Dupuytren's disease identifies novel risk locus and reveals a shared genetic etiology with BMI

Abstract: Dupuytren's disease is a common inherited tissue‐specific fibrotic disorder, characterized by progressive and irreversible fibroblastic proliferation affecting the palmar fascia of the hand. Although genome‐wide association study (GWAS) have identified 24 genomic regions associated with Dupuytrens risk, the biological mechanisms driving signal at these regions remain elusive. We identify potential biological mechanisms for Dupuytren's disease by integrating the most recent, largest GWAS (3,871 cases and 4,686 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 97 publications
2
21
1
Order By: Relevance
“… 39 , 40 Although the causative gene in this locus is not yet known, EPDR1 is a top candidate that has been functionally implicated in myofibroblasts. 41 , 42 This locus (at ELMO1 ) was also a human GWAS hit for primary biliary cholangitis. 43 ELMO1 (engulfment and cell motility 1) has been reported to confer susceptibility to human diabetic nephropathy, 44 which is a disease of excess ECM deposition, similar to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 Although the causative gene in this locus is not yet known, EPDR1 is a top candidate that has been functionally implicated in myofibroblasts. 41 , 42 This locus (at ELMO1 ) was also a human GWAS hit for primary biliary cholangitis. 43 ELMO1 (engulfment and cell motility 1) has been reported to confer susceptibility to human diabetic nephropathy, 44 which is a disease of excess ECM deposition, similar to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have reported that a high body mass index (BMI) is associated with a lower risk of DD (Gudmundsson et al, 2000;Hacquebord et al, 2017). This association is supported by a recent transcriptome-wide association study, which revealed a negative genetic correlation between BMI and DD risk (Major et al, 2019). However, the causal relationship for this correlation has yet to be explored, and no biological mechanisms have been proposed to explain how high BMI could protect against the development of DD.…”
Section: Introductionmentioning
confidence: 90%
“…Dupuytren's contracture is a benign, albeit irreversible progressive disease of the palmar aponeurosis that causes increasing flexion contractures, progressive flexion deformities and a decreased range of motion of the fingers (1,2). It is a common disorder of connective tissue, affecting 5-25% of individuals of European descent and genome-wide association study revealed several relevant loci (3)(4)(5)(6)(7). Furthermore, patients with diabetes mellitus, liver diseases or epilepsy as well as those with chronic exposure to strong hand-arm vibrations, high levels of alcohol consumption and smoking are at risk to develop such flexion deformities (1,2,(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%